Evaluation of the Use of Postpartum Family Planning Methods for Postpartum Mothers at the Buntalo Community Health Center, Lolak District - Yuliana Elusai Sasoloa; Anik Sri Purwanti (PPNI UNIMMAN, 2026)
Background: Contraception is an effective method for controlling fertility and reducing the risk of unintended pregnancies. However, the utilization of long-term contraceptive methods remains relatively low. Several factors such as education level, parity, and age are believed to influence women’s decisions in choosing Contraception. Objective: This study aimed to analyze the influence of education, parity, and age on the use of Contraception. Methods: This study employed an analytical observational design with a cross-sectional approach. The sample consisted of 30 women of reproductive age selected using a total sampling technique. Data were collected through structured questionnaires and analyzed using the Chi-square test to determine the association between education, parity, age, and the use of Contraception. Results: The results showed a significant relationship between education level, parity, and age with the use of Contraception. Statistical analysis using the Chi-square test obtained a p-value of 0.003 (p < 0.05), indicating that education, parity, and age significantly influenced the use of long-term contraceptive methods. Conclusion: Education level, parity, and age have a significant influence on the use of Contraception. Improving health education and counseling regarding long-term contraceptive methods is essential to increase their utilization among women of reproductive age.